Efficacy and safety of eptinezumab in patients with migraine and self-reported aura: Post hoc analysis of PROMISE-1 and PROMISE-2. (July 2022) - Ashina, Messoud; McAllister, Peter; Cady, Roger; Hirman, Joe; Ettrup, Anders
Background: This post hoc subgroup analysis evaluated the efficacy and safety of eptinezumab for migraine prevention in patients with migraine and self-reported aura. Methods: PROMISE-1 (NCT02559895; episodic migraine) and PROMISE-2 (NCT02974153; chronic migraine) were randomized, double-blind, placebo-controlled trials that evaluated eptinezumab for migraine prevention. In both studies, the primary outcome was the mean change from baseline in monthly migraine days over Weeks 1–12. Patients in this analysis included those who self-reported migraine with aura at screening. Results: Of patients with episodic migraine, ∼75% reported a history of aura at screening; of patients with chronic migraine, ∼35% reported a history of aura. Changes in monthly migraine days over Weeks 1–12 were –4.0 (100 mg) and –4.2 (300 mg) with eptinezumab versus –3.1 with placebo in patients with episodic migraine with aura, and were –7.1 (100 mg) and –7.6 (300 mg) with eptinezumab versus –6.0 with placebo in patients with chronic migraine with aura. Treatment-emergent adverse events were reported by 56.0% (100 mg), 57.4% (300 mg), and 55.4% (placebo) of patients. Conclusions: The preventive migraine efficacy of eptinezumab in patients in the PROMISE studies who self-reported aura was comparable to the overall study populations, demonstrating a similarly favorable safety and tolerability profile. Trial registration: ClinicalTrials.gov Identifiers: NCT02559895 and NCT02974153